2007
DOI: 10.1111/j.1537-2995.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered processing of thawed red cells to improve the in vitro quality during postthaw storage at 4°C

Abstract: Leukoreduced, deglycerolized RBCs can be stored for 48 hours in SAGM. Improved ATP levels during refrigerated storage can be observed with thawed cells, resuspended in AS-3, when PBS is used as a washing solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 24 publications
9
71
0
Order By: Relevance
“…A review of the literature will reveal inter-institutional variability of red blood cell recovery. 18,19 The current American Association of Blood Banks standard mandates a post thaw recovery 80% of the original red cells present prior to glycerolization. Although post thaw hematocrit in our study was lower than controls, this is not a clear marker for decreased recovery of cells as the reconstituted volume is not strictly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature will reveal inter-institutional variability of red blood cell recovery. 18,19 The current American Association of Blood Banks standard mandates a post thaw recovery 80% of the original red cells present prior to glycerolization. Although post thaw hematocrit in our study was lower than controls, this is not a clear marker for decreased recovery of cells as the reconstituted volume is not strictly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…ATP and 2,3-DPG concentrations of the erythrocytes were measured using a previously published method with slight modifi cation (Lagerberg et al 2007). Each thawed erythrocyte sample (0.2 ml) was added to 1 ml of perchloric acid ( …”
Section: Erythrocyte Metabolite Assaymentioning
confidence: 99%
“…Th e optical densities (OD) of total hemoglobin (tHb) and supernatant hemoglobin (sHb) were read spectrophotometrically at a wavelength of 540 nm (Model 2020; Anthos Labtec Instruments, Wals, Salzburg, Austria). Percentages of hemolysis and cell survival rate were calculated using the following formulas (Lagerberg et al 2007):…”
Section: Erythrocyte Recovery Testmentioning
confidence: 99%
“…36 Other studies have identified a host of molecular and biochemical changes that occur during packed red blood cell (pRBC) storage, collectively known as the red blood cell storage lesion, as the etiology of massive transfusion related morbidity. 68 Although these changes are documented in the literature, there is little understanding as to how agents in donor blood interacts with the transfusion recipient to cause harm.…”
Section: Introductionmentioning
confidence: 99%